738 DETERMINANTS OF MUSCLE DENSITY IN OLDER PEOPLE: FINDINGS FROM THE HERTFORDSHIRE COHORT STUDY (HCS). (8th March 2022) - Laskou, F; Westbury, L D; Fuggle, N; Harvey, N C; Patel, H P; Cooper, C; Ward, K; Dennison, E M
Abstract: Introduction: Lower calf muscle density (CMD) as assessed by peripheral quantitative computed tomography (pQCT) is associated with greater hip fracture risk, independent of FRAX, falls and bone mineral density. To date, muscle density has been little studied, and its determinants are unknown. In this study, we examine the lifestyle and anthropometric determinants of future muscle density (MD) in the HCS. Methods: 197 men and 178 women, aged 59–70 years, were recruited. A lifestyle questionnaire collected information on physical activity, smoking, alcohol consumption and dietary patterns. Height and weight were measured. pQCT of the radius and tibia was performed a median of 11.5 (IQR 10.9, 12.3) years later. MD was measured at calf and forearm using standard methodology. Baseline characteristics in relation to MD at follow-up were examined separately using linear regression with sex, baseline age and follow-up time included as covariates in all models. Results: Mean (SD) age at baseline was 64.7 (2.7) years; mean (SD) MD values (mg/cm3) were as follows: forearm [men 79.9 (3.1), women 77.2 (3.2)], calf [men 80.7 (2.6), women 78.5 (2.6)]. Baseline correlates (p < 0.05) of both lower forearm and CMD included female sex, lower weight, and lower BMI. SD difference in CMD for women compared to men, and per SD lower weight and BMI were − 0.84 [95%CI: −1.13, −0.54]), −0.37 [−0.46, −0.27] and − 0.31 [−0.40, −0.23] respectively. Additional correlates of lower CMD included older age and shorter stature. Relationships between MD and age were stronger at the calf (p < 0.001) than the forearm (p = 0.08). Lifestyle measures were not associated with MD. Conclusion: Female sex, older age, and lower BMI were associated with lower MD in older community-dwelling adults, highlighting the need for sustained muscle conditioning in older individuals. Further studies in larger cohorts are required.